2018
DOI: 10.3901/jme.2018.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vehicle and Track Key Parameters on the Rail Corrugation of High-speed Railways

Abstract: Abstract:Based on wheel-rail vertical dynamics, wheel-rail rolling contact theory and abrasion theory of materials, a calculation model of high speed railway rail corrugation is established and the corresponding numerical method is developed. The wheel-rail vertical dynamic model is established using the parameters of a corrugated ballastless high-speed railway. Hertz contact theory and Carter two-dimensional theoretical model of wheel-rail contact are used to calculate the wheel-rail contact force in normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although they have made a lot of achievements in theory and practice, they have not reached a consensus on the formation mechanism of rail corrugation so far, especially the research on rail corrugation of high-speed rail, which has been gradually carried out in recent years. Jiang et al 5 established the theoretical model of rail corrugation development on the ballastless track of high-speed rail, reproduced the evolution process of rail corrugation through numerical simulation, and investigated the influence of key parameters of vehicle and track on the development of rail corrugation. The results showed that reducing the stiffness of vehicle primary suspension and increasing the rail hardness were effective measures.…”
Section: Introductionmentioning
confidence: 99%
“…Although they have made a lot of achievements in theory and practice, they have not reached a consensus on the formation mechanism of rail corrugation so far, especially the research on rail corrugation of high-speed rail, which has been gradually carried out in recent years. Jiang et al 5 established the theoretical model of rail corrugation development on the ballastless track of high-speed rail, reproduced the evolution process of rail corrugation through numerical simulation, and investigated the influence of key parameters of vehicle and track on the development of rail corrugation. The results showed that reducing the stiffness of vehicle primary suspension and increasing the rail hardness were effective measures.…”
Section: Introductionmentioning
confidence: 99%